Modern technologies used in the process of physical education and rehabilitation for violations of posture and flat feet in children of older preschool age - Футорний, Сергій; Носова, Наталія; Коломієць, Тетяна (Slobozhanskyi Herald of Science and Sport, 2017)
Sergey Futornyi, Natalia Nosova & Tetiana Kolomiiets Purpose: analyze and summarize scientific information on the problem of technologies that are used in the process of physical education and rehabilitation for violations of posture and flat feet in children of older preschool age, according to special scientific and methodological literature. Material & Methods: theoretical analysis and generalization of literary and documentary sources included the use of a number of the following methods: the method of reconstruction, the method of apperceptions, aspect analysis, hermeneutic analysis, problem analysis. Results: despite a significant number of scientific studies on the prevention and correction of human posture disorders, recent results and their undoubted value for science and practice, it can be stated that the proposed technologies and methods do not fully allow to effectively cope with the steadily growing number of children senior preschool age with various functional disorders of the locomotor system. Conclusion: every year the number of children of senior preschool age with functional disorders of posture increases. Inadequate efficiency of health-improving measures for violations of the posture of children of senior preschool age by many researchers is due to the insufficiently developed technology for assessing her condition. Obtained data indicate the need to develop a technology for measuring and analyzing the level of the biogeometric profile of the posture of children aged 5–6 years in the frontal and sagittal planes.